Comparative evaluation of the prognostic significance of molecular tumor markers (estrogen and progesterone receptors, HER-2/neu) and the Nottingham prognostic index in breast cancer - V. Sekhri; N. Jain; S. Kapoor (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. The Nottingham prognostic index (NPI) is a tool that, based on quantitative histological features of the tumor, allows optimal treatment tactics for patients suffering from breast cancer (BC). The level of estrogen and progesterone receptors (ER/PR), as well as the expression of HER-2/neu receptors are important parameters in the molecular evaluation of this tumor. The OBJECTIVE was to calculate the NPI in newly diagnosed patients with BC and to compare the prognostic efficacy of molecular markers (ER, PR) and Nottingham prognostic index. METHODS AND MATERIALS. The study included 125 patients with early BC. The Nottingham prognostic index was calculated based on the data of pathomorphological conclusions, and the levels of molecular markers were obtained by immunohistochemical analysis. Prognostic efficacy of molecular markers and Nottingham prognostic index was compared. RESULTS. According to immunohistochemical analysis, ER-positive tumors were detected in 66 (53%) patients, PRpositive – in 55 (44%) patients, a high level of expression of HER-2/neu receptors was registered in 22 (18%) cases. The mean NPI was 4.99±1.23. We found out that molecular markers corresponding to an excellent prognosis and by the Nottingham prognostic index were assigned to the moderate prognostic group. No statistically significant results was observed between the Nottingham prognostic index and molecular markers that would help in assessing the prognosis (p>0.05). CONCLUSION. In breast cancer, the Nottingham prognostic index is the best tool for prognosis determination than immunohistochemical markers.